ANT3 and STS are autosomal in prosimian lemurs: implications for the evolution of the pseudoautosomal region - Toder, Roland; Rappold, Gudrun; Schiebel, Katrin; Schempp, Werner (Human genetics, 1995)
Comparative in situ hybridization in various primate species has revealed a pseudoautosomal location for the human ANT3 gene and an X-specific location for the steroid sulfatase (STS) gene throughout the higher primate species up to the New World monkeys. However, ANT3 and STS map together on an autosome of two prosimian species of the genus Lemur and Eulemur. These results suggest an autosome-to-X/Y translocation after the simians radiated from the prosimians, resulting in a pseudoautosomal location of genes such as ANT3 and STS. In simian primates, STS then became X-specific by a pericentric inversion in the Y chromosome followed by mutational inactivation of the Y allele.
Gesehen am 30.03.2021